Importance of functional food compounds in cardioprotection through action on the epigenome. (15th October 2018) - Lionetti, Vincenzo; Tuana, Balwant S; Casieri, Valentina; Parikh, Mihir; Pierce, Grant N
Abstract: Food constituents can either promote cardiovascular health or serve in its demise. In view of the lack of more effective pharmacological interventions in cardiovascular disease (CVDs), attention has focused on the potential protective effects of diet. Food components and their metabolites are emerging as major regulators of the human epigenome, which is being linked to CVDs. In this review, we summarize data from studies that suggest an important role for bioactive food compounds in cardioprotection and the potential for harnessing the epigenome as a nutrient sensor target in CVDs. While clinical data strongly support a role for effective diet intervention in CVDs protection, studies linking changes to human epigenome are now warranted for mechanistic insight and development of personalized care.